Risk Factors for Cesarean Delivery following Labor Induction in Multiparous Women - Corine J. Verhoeven; Cedric T. van Uytrecht; Martina M. Porath; Ben Willem J. Mol (Journal of Pregnancy)
Objective. To identify potential risk factors for cesarean delivery following labor induction in multiparous women at term. Methods. We conducted a retrospective case-control study. Cases were parous women in whom the induction of labor had resulted in a cesarean delivery. For each case, we used the data of two successful inductions as controls. Successful induction was defined as a vaginal delivery after the induction of labor. The study was limited to term singleton pregnancies with a child in cephalic position. Results. Between 1995 and 2010, labor was induced in 2548 parous women, of whom 80 had a cesarean delivery (3%). These 80 cases were compared to the data of 160 parous women with a successful induction of labor. In the multivariate analysis history of preterm delivery (odds ratio (OR) 5.3 (95% CI 1.1 to 25)), maternal height (OR 0.87 (95% CI 0.80 to 0.95)) and dilatation at the start of induction (OR 0.43 (95% CI 0.19 to 0.98)) were associated with failed induction. Conclusion. In multiparous women, the risk of cesarean delivery following labor induction increases with previous preterm delivery, short maternal height, and limited dilatation at the start of induction.